Pengaruh Brand Image Dan Komunikasi Pemasaran Terhadap Keputusan Pembelian Di Simposium Coffee - Agustina Pujiastuti; Mufid Andrianata; Aghnia Azzar Ulfah; Anang Maulana Romadhoni; Widya Nur Ainy (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
This study aims to determine the effect of Brand Image and Marketing Communication on Purchase Decisions at the Coffee Symposium. The researcher uses an associative quantitative research method with a sampling technique that uses non-probability sampling and incidental sampling consisting of 100 respondents at the Coffee Symposium. The data collection technique used in this research is by distributing questionnaires and processing data using SPSS computer software. This study contains the independent variables brand image and marketing communication, with purchasing decisions as the dependent variable. The results of the validity test show that rcount > rtable means that all variables in this test are valid with a Cronbach Alpha value > 0.60 which means that they are reliable in the reliability test. Based on the T-test, the results showed that there was a significant effect on the brand image and the marketing communication influence on purchasing decisions at Symposium Coffee.